Experience of treatment of endometriosisrelated pneumothorax - V. G. Pishchik; A. D. Obornev; M. A. Atyukov; A. S. Petrov; A. I. Kovalenko (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The article analyzed the experience of treatment of endometriosis-related pneumothorax (ERP). MATERIAL AND METHODS. The diagnosis of ERP was detected in 30 women at the period from 2004 to 2015. A control group consisted of 149 women. RESULTS. Statistically significant differences associated with presence of ERP were the elder age, right-side localization and recurrence course of disease. Diaphragmatic fenestrations and endometriotic ectopy and their combinations were specific findings in ERP-group. This group of patients characterized by frequent recurrences and higher rate of complications. The most effective method of treatment of ERP was diaphragm resection with pleurectomy and hormone therapy from 3 to 6 months after surgery. CONCLUSIONS. Endometriosis-related pneumothorax could cause up to 34 % cases of spontaneous pneumothorax in women of reproductive age. Diaphragmatic fenestrations and endometriotic lesions were specific signs of EAP. Direct visual examination of the pleural cavity was inevitable for reliable diagnostics of the disease. Surgical treatment of ERP was determined by higher rates of complication and recurrence. Postoperative hormone therapy could significantly improve the results of surgical treatment of ERP.